FERROPERICLASE - A LOWER MANTLE PHASE IN THE UPPER MANTLE - Brey G.P.; Harris J.W.; Stachel T.; Bulatov V.; Girnis A. (My University, 2004)
Experiments on compositions along the join MgO–NaA3+Si2O6 (A=Al, Cr, Fe3+) show that sodium can be incorporated into ferropericlase at upper mantle pressures in amounts commonly found in natural diamond inclusions. These results, combined with the observed mineral parageneses of several diamond inclusion suites, establish firmly that ferropericlase exists in the upper mantle in regions with low silica activity. Such regions may be carbonated dunite or stalled and degassed carbonatitic melts. Ferropericlase as an inclusion in diamond on its own is not indicative of a lower mantle origin or of a deep mantle plume. Coexisting phases have to be taken into consideration to decide on the depth of origin. The composition of olivine will indicate an origin from the upper mantle or border of the transition zone to the lower mantle and whether it coexisted with ferropericlase in the upper mantle or as ringwoodite. The narrow and flat three phase loop at the border transition zone—lower mantle together with hybrid peridotite plus eclogite/sediments provides an explanation for the varying and Fe-rich nature of the diamond inclusion suite from Sao Luiz, Brazil.
Keywords: Ferropericlase; Olivine; Diamond; Upper mantle; Lower mantle; Inclusions